Drying kinetics of Aquilaria Subintegra leaves: article / Ainul Mardhiah Abdul Rahim and Habsah Alwi - Abdul Rahim, Ainul Mardhiah; Alwi, Habsah (2018)
Technology on drying systems becoming more advanced for the preparation of quality-dehydrated food product continuously optimize the power level above a target value. Typical drying curves occurs in high drying rate which leads to quality damage based on the texture and color. To overcome the issues, the vacuum far infrared system is being proposed that is being assumed to get the optimum in terms of product quality, energy usage and drying time. The aim of this work was to investigate the vacuum far infrared drying towards Aquilaria Subintegra leaves. Leaves is subjected with different drying temperature (40, 50 and 60°C), to investigate the effect towards the drying kinetics, color and the quality of the leaves. The shortest time taken to achieve constant read of moisture content is 60°C, followed by 50°C and 40°C. Drying temperature also affecting the moisture ratio which the higher the temperature, the reduced the drying time to bring moisture ratio to constant. The drying rate which the higher the temperature, the higher the drying rate. It is found that Page mathematical model fitted best for the sample. The color changes determine that the longer the drying time, L* decreases, a* and b* increases. The browning effect occurs faster for higher drying temperature. As drying time increases, the color degraded significantly as well as the texture become crumpled and drier. The effect is faster as the higher drying temperature. However, the total color difference, chroma and hue angles values were similar at the end of processing for all temperatures.